Aggressiveness of the Electricity Sector and Implications for Energy GDP (Comparative Test of Indonesia-Malaysia) - Jiuhardi, Jiuhardi; Michael, Michael (International Journal of Energy Economics and Policy, 2022)
Keep in mind, energy is fluctuating. The dependence of electricity production from fossil fuels is a valuable lesson for stakeholders to think about and inspire the creation of the latest technology. Although the contribution of fossil fuels has grown the flow of industry in various worlds, they must limit it as early as possible. We set this research up based on a quantitative approach that aims to examine the impact of fossil fuels electricity generation on GDP per unit of energy used, electricity production capacity, and access to electricity. Indonesia and Malaysia as countries that represent empirical objectivity to be reviewed on how the causality of the research objectives for the period 2013-2020. We collected the data source through The Global Economy, which is very concerned with highlighting global economic developments. Multiple regression and path analysis support this work. Interestingly, the three findings for the case study in Indonesia support the design hypothesis (p <0.05), whereas the two hypotheses in Malaysia (p <0.05). The determinant of GDP per unit of energy used has met two-way causality. There are short-term and long-term prospects from other relationships that are not significant (p> 0.05). Besides the economic element, it does not balance the results due to demographic factors in Indonesia, which are larger in composition than Malaysia. Future agenda need to discuss the implications of further referring to this research.